Titer Widal pada Populasi Sehat di Universitas Jember - Dissa Yulianita Suryani; Muhammad Ali Shodikin; Ida Srisurani Wiji Astuti (Pustaka Kesehatan, 2018)
Enteric fever is endemic in developing countries including Indonesia. Widal test in a single serum sample is commonly used as laboratory diagnosis especially where culture facilities are not available. Examination of the single Widal test in endemic countries such as Indonesia, will give less accurate results with the large number of false-positive or false-negative. One of false-positive results is single Widal interpretation of test in endemic areas where the majority of the healthy population had contact or infected previously, and showed a positive result of Widal test. Widal titre examination in healthy population both men and women have not been investigated in Jember. So the aim of this study was to determine Widal titres among apparently healthy population in Jember University. In this cross-sectional study, blood samples were collected as much as 3 mL from healthy men (n=47) and women (n=47) and were analyzed for the presence of Salmonella antibodies by carrying out the Widal slide agglutination test. The data was analyzed using SPSS version 23 descriptively. The result showed that the most frequent antibody titres of O, H, AO, AH, BO, and BH antigens were 1/320 (37,2%), 1/320 (38,2%), 1/320 (86,1%), 1/320 (67,0%), 1/320 (77,7%) and 1/40 (27,7%) respectively in healthy population. In conclusion, antibody titre of AO dominated the most positive results in healthy population. Keywords: Widal test, healthy population, Indonesia